The genetic landscape of mitochondrial diseases in the next-generation sequencing era: a Portuguese cohort study - Nogueira, C.; Pereira, C.; Silva, L.; Laranjeira, Mateus; Lopes, A.; Neiva, R.; Rodrigues, E.; Campos, T.; Martins, E.; Bandeira, A.; Coelho, M.; Magalhães, M.; et al. (Frontiers in Cell and Developmental Biology, 2024)
Rare disorders, genetically and clinically heterogeneous, such as mitochondrial diseases (MD), have a challenging diagnosis. Nuclear genes codify most proteins involved in the mitochondrial biogenesis, despite all mitochondria having their own DNA. The development of Next Generation Sequencing (NGS) technologies has revolutionized the understanding of many genes involved in the pathogenesis of MD. In this new genetic era, using a NGS approach, we aimed to identify, in a cohort of 450 Portuguese patients, their genetic etiology for a suspected MD. Using a combined NGS strategy, we started with the analysis of a targeted mitochondrial panel of 213 nuclear genes and then we proceed to analyze the whole mitochondrial DNA.In this study, we identified disease related variants in 134 (30%) analyzed patients, 88 with nuclear DNA (nDNA) and 46 with mitochondrial DNA (mtDNA) variants, being most of them pediatric patients (66%), from which 77% were identified in nDNA and 23% in mtDNA. The molecular analysis of this cohort revealed 72 already described pathogenic and 20 novel probably pathogenic variants, as well as 62 variants of unknown significance. For this cohort of patients with suspected MD, the use of a customized gene panel provided a molecular diagnosis in a timely and cost-effective manner. Patients who could not be diagnosed after this initial approach will be further selected for whole exome sequencing.As a national laboratory for the study and research of MD, we demonstrated the power of NGS to achieve a molecular etiology, expanding the mutational spectrum and proposing, in this group of heterogeneous diseases without therapeutically options, an accurate genetic counseling.